2008
DOI: 10.3923/pjbs.2008.1935.1939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bean (Phaseolus vulgaris) Seeds Inoculation with Rhizobium phaseoli and Plant Growth Promoting Rhizobacteria on Yield and Yield Components

Abstract: To study the effect of co-inoculation with plant growth-promoting rhizobacteria (PGPR) and Rhizobium, on yield and yield components of common bean (Phaseolus vulgaris L.) cultivars was investigated in 2 consecutive years under field condition of plant growing evidence indicates that soil beneficial bacteria can positively affect symbiotic performance of rhizobia. PGPR strains Pseudomonas fluorescens P-93 and Azospirillum lipoferum S-21 as well as two highly effective Rhizobium strains were used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 11 publications
6
45
0
5
Order By: Relevance
“…The same authors describe that the resistance to water deficit can be increased and Yadegari et al (2008) affirm that this is due to the involved bacteria. Otherwise, even with a low rainfall index observed on February and March of 2013/2014 (Figure 1), these benefits were not observed in the present study.…”
Section: Resultsmentioning
confidence: 89%
“…The same authors describe that the resistance to water deficit can be increased and Yadegari et al (2008) affirm that this is due to the involved bacteria. Otherwise, even with a low rainfall index observed on February and March of 2013/2014 (Figure 1), these benefits were not observed in the present study.…”
Section: Resultsmentioning
confidence: 89%
“…The increase in individual pod weight due to might be due to increased number of seeds per pod and 100 seed weight as referred by Yadegari and Rahamani (2010).Besides higher pod length (13.74 cm) and pod width However, significantly the longest pod length (14.25 cm), wider pod width (1.27 cm) and highest individual pod weight (6.79 g) was recorded by Arka Komal, whereas shortest pod length (12.78 cm) was observed in Victoria and smallest pod width (0.64 cm) and lowest individual pod weight (3.79 g) were noticed in Falguni. The variation in pod length, pod width and individual pod weight of French bean varieties observed in the present study may be due to their inherited traits and to some extent by environmental factors.…”
Section: Fruit Characters Yield Attributes and Yieldmentioning
confidence: 99%
“…Voisin et al, (2003) and Yadegari and Rahmani (2010) reported that with respect to the amount of N 2 symbiotically fixed by leguminous plants, such as common beans inoculated with efficient Rhizobium strains, increased N fixation is strongly correlated with the number of nodules and nodular biomass. However, the results displayed with the inoculation of Rhizobium sp.…”
Section: Resultsmentioning
confidence: 99%